Assessing the Potential Effectiveness of the ASEAN-China Code of Conduct on the South China Sea in Constraining Chinese Aggressive Actions - Trystanto Trystanto (Padjadjaran Journal of International Law, 2022)
This article assesses the potential of the Code of Conduct in the South China Sea in constraining Chinese aggressive actions and maintaining the peaceful order of conduct of claimants and countries bordering the highly-disputed South China Sea. Given the recent Chinese aggressive military and pseudo-military moves in the South China Sea to enforce its arguable illegal nine-dash line claim in the South China Sea, there are hopes that the Code of Conduct agreement between China and ASEAN states will provide a legal protection and guideline in the dispute management in the South China Sea. In spite of this aspiration, a closer inspection of the Code of Conduct reveals that one should not have a high degree of confidence in the potential of the Code of Conduct in managing and regulating the conduct of parties in the South China Sea. Seen through the lens of realism, especially given the anarchic nature of the international arena and the unclear type of international law that the Code of Conduct will assume, this article argues that countries, Indonesia especially, should not have a high degree of expectation that the Code of Conduct will act as some sort of legal power that could restrain China from utilizing military and pseudo-military power in enforcing its claim in the South China Sea.